Assessment of the Efficacy of Demonstration Techniques in Enhancing ASHAs’ Knowledge and Practice of First Aid Management for Dog Bites and Minor Injuries in Rural Bhopal - Jayanti Soniya (International Journal of Community Health Nursing And Practices, 2024)
Background: The individuals administering first aid, commonly referred to as first aiders, assume responsibility for the entire situation, including the injured individual and the nature of the injury or illness. They possess the understanding of what actions to avoid, in addition to what actions to take, thus preventing common errors often made by untrained individuals despite good intentions. Furthermore, they recognize that their knowledge and proficiency in first aid can significantly impact the outcome, potentially determining the contrast between life and death, temporary and permanent disability, and swift recovery versus prolonged hospitalization. Objectives of the Study: (i) To evaluate the initial knowledge of accredited social health activist (ASHA) workers concerning the first aid management of dog bites and minor injuries due to falls. (ii) To determine the impact of demonstration sessions on enhancing the knowledge of ASHA workers regarding the first aid management of dog bites and minor injuries from falls. (iii) To compare the knowledge scores of ASHA workers before and after the demonstration sessions. (iv) To investigate the relationship between the pre-test and post-test knowledge scores and selected variables. Research Hypotheses: H1: There is expected to be a notable rise in post-test knowledge scores concerning first aid for minor injuries among ASHA workers in a chosen rural region. H2: A notable correlation is anticipated between demographic variables and post-test knowledge scores concerning first aid for minor injuries among ASHA workers in a specified rural locality. Method of Data Analysis: Data were analyzed according to the objectives of the study and by using appropriate statistical techniques and are presented in the form of tables, graphs, and diagrams. Descriptive (mean, standard deviation, frequencies, percentage) and inferential (unpaired t-test, chi-square test) statistical methods were used to find significance in fetal outcome in normal and anemic mothers. The Karl Pearson correlation coefficient was employed to determine the correlation between maternal anemia and fetal outcomes. Results: Analysis involves a thorough investigation of the components and structure of something. In research, analysis entails calculating specific measures and identifying patterns of relationships among groups of data. This article deals with the analysis and interpretation data obtained from 60 ASHAs with the help of self-administered structured questionnaire to assess knowledge and practice regarding first aid for minor injuries. Conclusion: This article outlines the conclusions, implications, limitations, suggestions, scope, and recommendations of the study. The main objective of the study was to evaluate the knowledge of ASHA workers in a chosen rural area of Bhopal.
Keywords: ASHA; First aid; demonstration; falling; minor injuries